Store data from experiments with microorganisms used in food industry - Bosakova-Ardenska, Atanaska (International Journal of Intelligent Systems and Applications in Engineering, 2013)
The aim of this paper is to present results from collaboration of computer engineers and experimenters in microbiology working with molecular-genetic methods. The experimenters in microbiological laboratory at the University of Food Technologies use ARDRA (Amplified Ribosomal DNA Restriction Analysis) analyses and DNA sequencing processed with BLAST (Basic Local Alignment Search Tool) algorithm to identify some microorganisms. Their results have been accumulated in designed database. This will improve the effectiveness and productivity of the molecular-genetic analyses in department of microbiology.